2016
DOI: 10.1016/j.ad.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Cinco casos de urticaria multiforme y revisión de la literatura

Abstract: Urticaria multiforme is a cutaneous disorder that affects infants and small children. It is characterized by large, annular urticarial plaques with a violaceous center and is frequently accompanied by fever. Urticaria multiforme follows a benign, self-limiting course, but the striking appearance of the lesions can cause alarm and considerable anxiety among parents. We present 5 cases of urticaria multiforme seen in our hospital over a period of 18 months. All the cases were preceded by an infection of the uppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 7 publications
0
9
0
5
Order By: Relevance
“…Urticaria multiforme (UM) may be distinguished by the transient nature of the lesions and lack of significant systemic symptoms . Individual lesions typically resolve within 24 hours, with full resolution of the appearance of urticarial plaques within 10 days without residua . The presence of dermatographism and acral edema also supports a diagnosis of UM …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urticaria multiforme (UM) may be distinguished by the transient nature of the lesions and lack of significant systemic symptoms . Individual lesions typically resolve within 24 hours, with full resolution of the appearance of urticarial plaques within 10 days without residua . The presence of dermatographism and acral edema also supports a diagnosis of UM …”
Section: Discussionmentioning
confidence: 99%
“…Urticaria multiforme has been reported in association with both viral and bacterial upper respiratory infection, otitis media, pharyngitis, gastroenteritis, vaccinations, and medications including furazolidone or amoxicillin . It is a clinical diagnosis made based on its distinct appearance and accompanying acral and facial edema and dermatographism .…”
Section: Discussionmentioning
confidence: 99%
“…Urticaria multiforme (UM) is an uncommon benign cutaneous hypersensitivity that occurs mainly in pediatric patients 1, 2. It is characterized by annular lesions with a violaceous center, and may be accompanied by short-term fever, as well as by hand and foot edema 2, 3. It is a poorly recognized condition, mainly due to lack of reports in the literature.…”
mentioning
confidence: 99%
“…In most cases there is a temporal relationship with infections (mycoplasma, adenovirus, streptococci, Epstein–Barr), medications (mainly antibiotics), and vaccinations. In 2016, Sempau et al found an association with previous use of amoxicillin 3 . Specifically in neonates, there has been proven infection by herpes virus 6, and decreased viral load accompanied by clinical improvement of the patient 4…”
mentioning
confidence: 99%
See 1 more Smart Citation